Teaching of mbira dzavadzimu to begginers by making use of mother pieces - Matiure, Perminus (Midlands State University, 2020)
Teaching of mbira dzevadzimu is coupled with a lot of uncertainty and problems among mbira teachers in Zimbabwe. What makes the teaching of mbira dzavadzimu difficult is the com0plex structure of most of the pieces played .This paper demonstrates how teaching of mbira dzavadzimu pieces can be simplified by taking advantage of pieces that have similar aspects .During his ethnographic study about mbira pieces in Hwedza and Harare, the writer discovered that there are three major classes of mbira pieces with each class derived from mother piece.